Self-Interference (SELFI) Microscopy for Live Super-Resolution Imaging and Single Particle Tracking in 3D - Linarès-Loyez, Jeanne; Ferreira, Joana S.; Rossier, Olivier; Lounis, Brahim; Giannone, Gregory; Groc, Laurent; Cognet, Laurent; Bon, Pierre (Frontiers in Physics, 2019)
Through the formation of fluorescent self-interference (SELFI), quantitative intensity and phase imaging enables the 3D localization of single fluorescent molecules inside a fixed tissue with an accuracy well beyond the diffraction limit.. Here we demonstrate that this concept can be extended to 3D super-resolution microscopy and 3D single particle tracking in various living samples ranging from adherent cells to organotypic brain slices, using diverse fluorescent emitters (fluorescent proteins, organic dyes or quantum dots). This basically covers the most popular single molecule imaging techniques used for live sample studies. We also show that SELFI can be used in combination with different illumination schemes including highly inclined illumination and total internal reflection.